USING COLOR CODING TO IMPROVE STUDENTS' ENGLISH VOCABULARY ABILITY - Dimas Muhamad Rizki Nurdiansyah; Sandi Aryanto Asyid; Aseptiana Parmawati (IKIP Siliwangi, 2019)
English is a subject in Indonesian school that learned from junior high school until the universities. Therefore one of importance basic aspects and skills in learning English for students is to understand avariety of English vocabulary. In learning English, vocabulary plays an important role, it means vocabulary is the basic one to mastering all English Skill. This research intended to students at seventh grade of Madrasah Tsanawiyah (MTs) in Cimahi. And this study aims to determine the benefits of Color Coding technique in improving the ability of English vocabulary. Color Coding is a method that can be used in teaching vocabulary, one of the use of color is to identifying something, it can make the student easy in their learning vocabulary process. The design of this research is Classroom Action Research (CAR). The researcher employed qualitative research design and pre experimental pretest-posttest. Thedata were collected from the result of pretest and posttets. The result of the data showed: Mean of pretest was 63.00, mean of posttest was 82.00, The result also show the score of t-observed was higher than ttable (2.08 > 1.72). It means color coding is effective to improve students’ vocabulary ability.Keywords: Vocabulary, Color Coding Technique, CAR